Functional Movement Screen scores and physical performance among youth elite soccer players - Silva, B.; Clemente, F. M.; Camoes, M.; Bezerra, P. (Sports, 2017)
This study had two main objectives: (1) to determine if differences in Functional Movement Screen (FMS) scores exist between two levels of competition; and (2) to analyze the association between FMS individual and overall scores and physical performance variables of lower-limb power (jumps), repeated sprint ability and shot speed. Twenty-two Under 16 (U16) and twenty-six Under 19 (U19) national competitive soccer players participated in this study. All participants wer evaluated according to anthropometrics, FMS, jump performance, instep kick speed and anaerobic performance. There were no significant differences in the individual FMS scores between competitive levels. There were significant negative correlations between hurdle step (right) and Running-based Anaerobic Sprint Test (RAST) power average (p = -0.293; p = 0.043) and RAST fatigue index (RAST FatIndex) (p = -0.340; p = 0.018). The hurdle step (left) had a significant negative correlation to squat jump (SJ) (p= -0.369; p = 0.012). Rotary stability had a significant negative correlation to RAST fatigue index (Right: p= -0.311; p = 0.032. Left: p = -0.400; p = 0.005). The results suggest that individual FMS scores may be better discriminants of performance than FMS total score and established minimal association between FMS scores and physical variables. Based on that, FMS may be suitable for the purposes of determining physical function but not for discriminating physical performance.